Education choice under uncertainty: Implications for public policy - Vincent Hogan; Ian Walker (University College Dublin, UCD School of Economics, 2006)
We analyse how progressive taxation and education subsidies affect schooling decisions when the returns to education are stochastic. We use the theory of real options to solve the problem of education choice in a dynamic stochastic model. We show that education attainment will be an increasing function of the risk associated with education. Furthermore, this result holds regardless of the degree of risk aversion. We also show that progressive taxes will tend to increase education attainment.
hdl:10197/953
Keywords: J24; C61; D81; 330; Education Choice; Dynamic Optimization; Optimal Stopping; Uncertainty